Soluble CD52 mediates immune suppression by human seminal fluid - Harrison, Leonard C.; Stone, Natalie L.; Bandala-Sanchez, Esther; Huntington, Nicholas D.; McLachlan, Robert I.; Rautela, Jai; O’Bryan, Moira K. (Frontiers in Immunology, 2024)
Seminal fluid provides for the carriage and nutrition of sperm, but also modulates immunity to prevent allo-rejection of sperm by the female. Immune suppression by seminal fluid has been associated with extracellular vesicles, originally termed prostasomes, which contain CD52, a glycosylated glycophosphoinositol-anchored peptide released from testicular epithelial cells. Previously, we reported that human T cell-derived CD52, bound to the danger-associated molecular pattern protein, high mobility group box 1 (HMGB1), suppresses T cell function via the inhibitory sialic acid-binding immunoglobulin-like lectin-10 (Siglec-10) receptor. Here we show that human seminal fluid contains high concentrations of CD52 complexed with HMGB1, which mediates T cell suppression indirectly via Siglec-7 on antigen-presenting cells. Proliferation of natural killer (NK) cells, which express Siglec-7 and play a key role in the immune defence of the uterus, was directly suppressed by seminal fluid CD52. These findings elucidate a critical function of seminal fluid to suppress cellular immunity and facilitate reproduction.